Pyk2 is a Novel Tau Tyrosine Kinase that is Regulated by the Tyrosine Kinase Fyn - Li, Chuanzhou (J Alzheimers Dis, 2018)
The protein tyrosine kinase Pyk2 is encoded by PTK2B, a novel Alzheimer’s disease (AD) susceptibility variant, with the PTK2B risk allele being associated with increased mRNA levels, suggestive of increased Pyk2 levels. However, the role of Pyk2, a member of the focal adhesion kinase (FAK) family, in AD pathology and its regulation are largely unknown. To address this, we generated mice with neuronal expression of human Pyk2. Because we had previously reported an association of Pyk2 and hyperphosphorylated tau (a hallmark feature of AD) in human tau transgenic pR5 mice, we also generated Pyk2/tau double-transgenic mice, which exhibit increased tyrosine phosphorylation and accumulation of tau. We further demonstrated that Pyk2 colocalizes, interacts with, and phosphorylates tau in vivo and in vitro. Importantly, although Pyk2 interacts with the established tyrosine-directed tau kinase Fyn, we identified an increased Pyk2 activity in mice which constitutively overexpress Fyn (FynCA), and a decreased activity in mice lacking Fyn (FynKO). Together, our study reveals a novel role for Pyk2 as a direct tyrosine kinase of tau that is active downstream of Fyn. Our analysis may enhance the understanding of how the PTK2B risk allele contributes to tauopathy.